Satellite altimetry for geodetic, oceanographic, and climate studies in the Australian region - Deng, X.; Griffin, D.; Ridgway, K.; Church, J.; Featherstone, Will; White, N.; Cahill, M. (Springer Berlin Heidelberg, 2011)
This chapter provides an overview of recent research applications utilizing satellite altimetry around Australia. Topics covered include improving the quality of altimeter sea surface height (SSH) data in coastal regions, observing and understanding the structure and variability of the major boundary current systems, estimating regional sea-level changes, and determining and verifying the marine gravity field using altimetry. The approaches highlighted in this chapter use altimetry synergistically with all available oceanic data including other remote sensing techniques, drifting buoys, and in situ data such as coastal tide-gauges. The results presented are an integration of altimetric and in situ data with a high-resolution computer model in order to simulate the sea-level changes in Australian coastal and offshore regions. Through such synthesizing research approaches, satellite altimetry continues to make an important contribution to a number of key strategic research areas in the Australasian region.